KAJIAN KENYAMANAN RUANG KULIAH TN II JURUSAN TEKNIK FISIKA UNIVERSITAS GADJAH MADA (UGM) DITINJAU DARI ASPEK TERMAL DAN POLA ALIRAN UDARA MENGGUNAKAN FLUENT - Sunanto Sunanto; Karsid Karsid (P3M Politeknik Negeri Indramayu, 2016)
Temperature and air circulation is an important factor in a building since it is closely related to health comfort. Therefore, the design of a building should be carry out precisely in getting a clean, healthy and comfortable air circulation in accordance to the requirement of the room.In order to carried out a good building designing, a research was needed to understand temperature distribution, the pattern of air flow and its velocity. In this research, a Classroom of TN II JTF UGM. This classroom have 1030 cm length, 790 cm of width, and 330 cm of height. The size of the windows is 100 x 100 cm and place 1m from the floor. The size of the doors is 140 x 210 cm. The windows are assumed to be widely open, the door always opened. The researched begins with geometric modeling of the model by using Gambit 2.2.30 and continued with model testing using Fluent 6.2.16. The test is carried out by giving three velocity variation of free air flowing i.e.: from 1.3 m/s, 3.61 m/s and 5.92 m/s, two direction variation of open air flowing and two variation temperature of free air i.e.: 21.50C and 27.650C.The standard of comfortable air velocity used in the room is 0.15 < V < 0.25 m/s, The standard of comfortable temperature used in the room is 20.50C and 27.10C. The air velocity and air temperature variation created comfort area and non comfort area in the room .The direction circulation of air variation created the different pattern air circulation in the room.